Investing in health professions education: A national development imperative for South Africa - van Staden, D. (South African Journal of Higher Education, 2021)
Background: Human resources for health are an essential component of any health system. South Africa’s National Development Plan identifies the need for a strengthened public health system and improvements in the quality of education and service delivery. While efforts to increase the number of trained health personnel are acknowledged, a lack of sustainable investment in improving the quality of health professions education in South Africa may have detrimental consequences for these national ideals. Discussion: South Africa’s economic growth has declined in recent years, placing pressure on its fiscal capacity and the ability of academic institutions to fund critical aspects relating to training needs within health professions education programmes. Increased intakes at universities have not been supported by concurrent increases in funding required to support evolving training needs. Reduced financial support for health professions education programs has implications for required resource capacity, and will potentially negatively impact the quality, as well as global competitiveness, of health professions training programmes in South Africa. Funding gaps which impact the quality of training also ultimately affect the quality of health services delivered by the health system in the long term. Conclusion: Political will in support of more sustainable funding mechanisms for ongoing investment into health professions education programs and their evolving training needs is required in order for South Africa to meet its development objectives as outlined in the National Development Plan and its National Health Insurance policy.